Characteristics and contributory factors for injectable contraceptive usage among women in Kumasi, Ghana. Issue 1 (December 2016) - Laryea, Dennis; Ankobeah, Frank; Morhe, Emmanuel; Amoako, Yaw; Spangenberg, Kathryn
Abstract Background Preferred methods of contraception vary from country to country. Family Planning services have been available on a large scale in Ghana since the 1980's and their use has contributed to gradual decline in the total fertility rate from 6.4 in 1988 to 4.2 in 2014. Since their introduction in Ghana in the early 1990's, Injectable contraceptives have seen increasing patronage and are currently the most preferred method of contraception. We set out to identify possible factors contributing to the preference for injectable contraceptives among women in Ghana. Methods We conducted a descriptive cross-sectional survey of women accessing contraceptive services at the Family Planning Unit of the Komfo Anokye Teaching Hospital in Kumasi, Ghana. Women who reported for the second dose of their injections were eligible to be selected for participation in the study. Informed consent was obtained from eligible participants. Data was collected using a structured questionnaire in January and February 2011. Data captured included age, marital status, highest level of education completed, religion, ethnicity and employment status, previous contraceptive use, sources of contraceptive information and reasons for choosing injectable contraceptives. Quantitative data was entered into a Microsoft Access Database and analysed using Epi Info Version 7.1.4. Qualitative data was analysed thematically. Results A total of 247 respondents participated in the study. One hundred and seventy three (70.0 %) were using Depot Medroxyprogesterone Acetate and 74 (30.0 %) were using NorethisteroneEnanthate/Estradiol Valerate. The mean age for women on Depot Medroxyprogesterone Acetate was higher than those on NorethisteroneEnanthate/Estradiol Valerate (p  < 0.001). The effectiveness of method, recommendation from other users, low incidence of forgetfulness and the relatively longer intervals for administration were the commonest reasons for the use of injectables among respondents. The majority of users, 225 (91.1 %), were satisfied with the method and will recommend it to other potential users. Only 10.8 % of the 68 respondents reporting undesirable effects of the injectables intend to change the method. Conclusion A high level of satisfaction exists among current users of injectables in Ghana and is influenced by a variety of factors. Strategies to increase the uptake of injectables can go a long way to increase the contraceptive prevalence rate and reduce the unmet need for Family Planning in Ghana.